Preparation of Protein Oleogels: Effect on Structure and Functionality - Annika Feichtinger; Elke Scholten (Foods, 2020)
Among available structuring agents that have been used to provide solid properties to liquid oils, protein is a more recent candidate. Due to their nutritional value and high consumer acceptance, proteins are of special interest for the preparation of edible oleogels as an alternative for solid fats. Whereas the field of protein oleogelation is still rather new and just starts unfolding, several preparation methods have been demonstrated to be suitable for protein oleogel preparation. However, there is limited knowledge regarding the link between microstructural properties of the gels and macroscopic rheological properties, and the potential of such protein-based oleogels as a fat replacer in food products. In this review, we therefore provide an overview of various protein oleogel preparation methods and the resulting gel microstructures. Based on the different structures, we discuss how the rheological properties can be modified for the different types of protein oleogels. Finally, we consider the suitability of the different preparation methods regarding potential applications on industrial scale, and provide a short summary of the current state of knowledge regarding the behavior of protein oleogels as a fat replacer in food products.